From Amherst (Massachusetts, USA) to Padua (Italy) and back again: Louis A. Carpino's scientifically productive journey. Issue 4 (5th March 2020) - Toniolo, Claudio; Moretto, Alessandro; Formaggio, Fernando; Broxterman, Quirinus B.; Crisma, Marco
Abstract: In this work, we studied and discussed a relevant aspect of peptide science, strictly related to the scientific production of Prof. Louis A. Carpino who passed away in early 2019. Specifically, we carried out a statistical survey on the significant 3D‐structural parameters (bond lengths, bond angles, and torsion angles) of the currently extensively used 9‐fluorenylmethyloxycarbonyl (Fmoc) α‐amino protecting group introduced by Carpino in peptide synthesis. In this compilation, we considered all 131 X‐ray diffraction structures available in the literature on amino acid / linear peptide derivatives and Fmoc‐labeled amines. Both Fmoc secondary and tertiary urethane functionalities were examined and separately analyzed. Abstract :